PENGARUH PEMUPUKAN TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS INTRODUKSI TANAMAN KANOLA (Brassica sp.) - DOAH DEKOK TARIGANS; ELNA KARMAWATI; DEDI S. EFFENDI (Jurnal Penelitian Tanaman Industri, 1999)
Effect offertilizer application on the growth and produc¬ tion of several introduced canola varieties (Brassica sp.)Canola (Brassica sp.) belongs to the exotic crop which poduces at with low content of unsaturntcd fat (7%). Technology for canola development in Indonesia, at present is not yet available. This research activity is the first expeiment on canola conducted in Indonesia. The objectives of the expeiment was to study the vegetative and generative characters of canola plant and the oil content of the canola seeds as affected by fetilizers applications. The expeiment was conducted at Gunung Putei Expeimental Station in Cipanas, W. Java, from October 1998 to Apil 1999. The altitude of the expeimental garden is 1 500 m above sea level, the soil type is andosol, and rainfall type A according lo Schmidt and Ferguson classification. The experiment used Randomized Block Design with two factors, variety of canola and fertilizer applications. The treatments under study was conducted with plot size 60 mi and three eplications. The treatments consisted of thee levels of fetilizer application with ive vaieties of canola, Hyola 401. Hyola 330. Hyola 308. Hyola 420. and Hyola 60009. The results of the expeiment showed that the highest number of pod production deived from Hyola 308 while the lowest was produced by Hyola 401, with average 123.6 and 85.3 pods, respectively. Number of seeds per pod vaies between vaieties range from 20.0 to 25.1. Whee the lowest was produced by Hyola 401 while the highest by Hyola 60009. Seed weight per 1000 seeds vanes between vaieties, with average 4.0-5.5 grams. The combination of fetilizer application and vaiety of canola affected the oil content of seed produced, ranged between 41.68 and 46 97%. Based on the performance of vegetative and generative growth and oil content of seed produced, it can be concluded that the canola plant is promising to develop in Indonesia.